KAJIAN SOLUSI DESAIN PENERAPAN PENCAHAYAAN ALAMI PADA MASJID AL-AZHAR - Idris, Nadila Aulia; Sirhadi, Jabar; Arlino, Dude; Jurumai, La Pande (RUSTIC, 2024)
Mosques, Muslim houses of worship, have always emphasized a solemn and peaceful atmosphere. Daylighting plays a vital role in creating this atmosphere, but is often overlooked or misunderstood. This research looks at how daylighting affects the religious experience in mosques and how architectural design can maximize it. Through case studies of specific mosques, this research analyzes aspects such as opening design, building orientation, and the use of skylights on the distribution and intensity of natural light. In addition, the research explores mosque users' perceptions of lighting quality and its effect on the solemnity of worship. The findings are expected to answer critical questions such as: Is the existing opening design optimal? Does the orientation of the building affect the level of lighting comfort? How does natural light affect the spiritual atmosphere of worshipers? These findings will be reflected into optimal daylighting design recommendations for mosques, supporting increased comfort and solemnity for worshippers.